Information experience of undergraduate students when optimizing google search for their study - Prasetyawan, Yanuar Yoga; Heriyanto; Arfa, Mecca (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: Google has become the most popular search engine worldwide and its name has its own merit within information search, as such when people are searching for information they would most often say ‘google it' rather than ‘look for it'. Purpose: The present research employs information experience perspective that investigates students of Universitas Diponegoro when they are using Google search to help complete their assignments. Method: The research method used to capture the information experience of Universitas Diponegoro students when using Google to look for information associated with their studies was the qualitative research method. Semi-structured interviews were used in this study to explore further information experience of students in exploring information using the Google search engine Findings: The findings revealed that undergraduate students have their own techniques when using Google search. They are well familiar with formulating search queries; the majority being able to take on this stage of task easily. However, students found it challenging when they have to start evaluating which of the search results would give the most relevant information to help with their assignments. Conclusions: Students' prior knowledge appeared to be the governing factor of how well they are able to determine which of the compiled information sources are best for their study. Every student has their own best approach and experience to optimize Google. Generally, it was found that the students within this study had similar ways in formulating keywords to search for information on Google and were only different in certain details of experiences.